2019
DOI: 10.1101/574723
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deep learning of representations for transcriptomics-based phenotype prediction

Abstract: The ability to predict health outcomes from gene expression would catalyze a revolution in molecular diagnostics. This task is complicated because expression data are high dimensional whereas each experiment is usually small (e.g., ∼20,000 genes may be measured for ∼100 subjects). However, thousands of transcriptomics experiments with hundreds of thousands of samples are available in public repositories.Can representation learning techniques leverage these public data to improve predictive performance on other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…When we used tissue studies of the human pancreas [11][12][13][14] and the mouse brain [15][16][17][18] , all machine-learning models and cellFishing.jl performed equally well on the prediction task. Smith et al 25 reported a similar result in bulk RNA-seq data. In contrast, the single-cell specific classifiers scMatch and Garnett showed lower accuracy on the same datasets.…”
Section: Most Machine Learning Methods Are Well-suited For Cell Type Annotation Given Optimal Hyper-parameter Valuesmentioning
confidence: 55%
“…When we used tissue studies of the human pancreas [11][12][13][14] and the mouse brain [15][16][17][18] , all machine-learning models and cellFishing.jl performed equally well on the prediction task. Smith et al 25 reported a similar result in bulk RNA-seq data. In contrast, the single-cell specific classifiers scMatch and Garnett showed lower accuracy on the same datasets.…”
Section: Most Machine Learning Methods Are Well-suited For Cell Type Annotation Given Optimal Hyper-parameter Valuesmentioning
confidence: 55%
“…Determination of the prediction that can confidently give rise to the gene expression in the body due to cancer can be done by deep learning process. As illustrated by Smith et al [12] that there are various traditional as well as scientific processes that can analyse the expression mechanism in the patients suffering from cancer. It has been analyzed that machine learning methods often provide a clear cut idea about the physiological and morphological changes that are occurring in the cells due to cancer.…”
Section: Critical Analysis Of the Deep Representation Of Learning On Phenotype Prediction From Gene Expressionmentioning
confidence: 99%
“…It has been analyzed that machine learning methods often provide a clear cut idea about the physiological and morphological changes that are occurring in the cells due to cancer. Smith et al [12] have also discussed the fact that genes are rarely active and act in isolation. It might be because along with the isolation procedure the physiological changes also happen in the genes in terms of its regulation.…”
Section: Critical Analysis Of the Deep Representation Of Learning On Phenotype Prediction From Gene Expressionmentioning
confidence: 99%
“…Deep learning may outperform other methods in big data classification with respect to accuracy of prediction [27], but not necessarily in other specific tasks, such as image-based cell-type annotation, for example [28]. It is not always clear which processing step in a deep learning approach would account for better results obtained [29].…”
Section: Big Data Analytics: From Machine Learning To Artificial Intementioning
confidence: 99%